Mistakes in Musculoskeletal Imaging: How to Minimize the Inevitable - Griffith, James F.; Vanhoenacker, Filip M. (Seminars in Musculoskeletal Radiology, 2025)
Most mistakes relate to either a lesion being missed or when a lesion is seen a wrong diagnosis being made. Clinicians and patients understandably want an accurate diagnosis. An accurate diagnosis, however, is not always possible given the complexities and inherent limitations of imaging. There is an inevitable trade off between committing to trying to provide a definitive diagnosis and occasionally getting it wrong. Better, and more useful, to being occasionally wrong though than habitually noncommittal.
Keywords: imaging: mistake; reports; diagnosis; error